Formation of bachelors’ competence readiness to work in a team - Saratovtseva, Nadegda V. (2020)
The purpose of the article is to analyze the experience of forming the competence of bachelors' readiness to work in a team. This competence is characterized by the ability of the student to realize their role in the team and to carry out social interaction, to focus on cooperation with team members. The requirements for training modern bachelors who are capable of continuous personal and professional growth through effective collective work are reflected in regulatory documents. In the structure of the competence of readiness to work in a team, we distinguish motivational, cognitive and functional components. Their formation is carried out in the course of studying the module "Man, society, culture", the disciplines "Fundamentals of management culture", "General psychology" and others. Where a significant role is played by the use of innovative educational technologies that contribute to building effective interaction between students. Special attention is paid to the development of such qualities of the student as sociability, openness, a sense of mutual assistance, positive emotional mood. Modern educational technologies of interaction have an active impact on the process of forming the bachelor's competencies of readiness to work in a team.